Circulating DNA as prognostic biomarker in patients with advanced hepatocellular carcinoma: a translational exploratory study from the SORAMIC trial - Marianna Alunni-Fabbroni (Journal of Translational Medicine, 2019)
Abstract Background Liquid biopsy based on cell-free DNA circulating in plasma has shown solid results as a non-invasive biomarker. In the present study we evaluated the utility of circulating free DNA (cfDNA) and the sub-type tumor DNA (ctDNA) in hepatocellular cancer (HCC) patients to assess therapy response and clinical outcome. Methods A cohort of 13 patients recruited in the context of the SORAMIC trial with unresectable, advanced HCC and different etiological and clinicopathological characteristics was included in this exploratory study. Plasma samples were collected between liver micro-intervention and beginning of sorafenib-based systemic therapy and then in correspondence of three additional follow-ups. DNA was isolated from plasma and next generation sequencing (NGS) was performed on a panel of 597 selected cancer-relevant genes. Results cfDNA levels showed a significant correlation with the presence of metastases and survival. In addition cfDNA kinetic over time revealed a trend with the clinical history of the patients, supporting its use as a biomarker to monitor therapy. NGS-based analysis on ctDNA identified 28 variants, detectable in different combinations at the different time points. Among the variants, HNF1A, BAX and CYP2B6 genes showed the highest mutation frequency and a significant association with the patients’ clinicopathological characteristics, suggesting a possible role as driver genes in this specific clinical setting. Conclusions Taken together, the results support the prognostic value of cfDNA/ctDNA in advanced HCC patients with the potential to predict therapy response. These findings support the clinical utility of liquid biopsy in advanced HCC improving individualized therapy and possible earlier identification of treatment responders.